Politik Kekerabatan Dalam Keterwakilan Perempuan Pada Rekrutmen Politik Partai Nasdem Pada Pemilu 2019 - Siti Zaetun; Chusnul Mar'iyah (TheJournalish: Social and Government, 2020)
The big wave of the women's movement in the world, apart from demanding rights and equality between men and women, also encourages women's representative participation in decision-making process. Previous studies often analyze women's representation based on cultural and institutional barriers without specifically showing the role of political parties in carrying out the gatekeeping activities, especially in women's candidacy. This article uses Pippa Norris' theory of political recruitment with descriptive qualitative analysis methods to analyze the increase in women's representation from Nasdem Party in the 2019 general elections. The results are (1) general election rules and political parties affect the increase in women's representation, (2) representation and women's interests have not become the main criteria in the political selection process of Nasdem Party, (3) the survey culture in the balancing of women's candidacy in addition to providing opportunities for female candidates also fostering kinship politics, (4) Nasdem’s commitment to women's representation and interests is still untested, and the most obvious is (5) as a political commodity where an increase in the representation of women with kinship political backgrounds contributed to the increase in the votes of Nasdem Party in the 2019 elections.